COVID-19 Monitoring Survey in Poor and Slum Areas of Dhaka and Chittagong : Labor Markets Impacts From Round 1 (10 June-10 July 2020) - World Bank (World Bank, Washington, DC, 2021)
To track the impacts of the COVID-19 crisis on labor markets and household coping strategies, a rapid phone survey was implemented on a representative sample of households living in poor and slum areas of Dhaka and Chittagong City Corporations (CCs). This brief summarizes results from the first round of the rapid phone survey, conducted from June 10 to July 10, 2020 (see Appendix one for details of the survey design). This first brief in the series focuses on the labor market impacts of COVID-19.